2005
DOI: 10.1111/j.0306-686x.2005.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Tests of Weak‐Form Efficiency of the Dhaka Stock Exchange

Abstract: Conflicting evidence on weak form efficiency of the Dhaka Stock Market appears to stem from the use of monthly versus daily data, structural changes after the 1996 market crash, and the use of tests with or without heteroscedasticity adjustment. Heteroscedasticity-robust tests indicate short-term predictability of share prices prior to the crash, but not afterwards. Although a heteroscedasticity-robust Box-Pierce test was used by Lo and MacKinlay (1989) in their simulations, our study appears to be the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…However, inter alios, MacKinlay (1988, 1989) 31 and Islam and Khaled (2005) note that a heteroscedasticity-consistent estimator of the variance of the sample autocorrelations r j is instead provided by…”
Section: Resultsmentioning
confidence: 99%
“…However, inter alios, MacKinlay (1988, 1989) 31 and Islam and Khaled (2005) note that a heteroscedasticity-consistent estimator of the variance of the sample autocorrelations r j is instead provided by…”
Section: Resultsmentioning
confidence: 99%
“…Kader and Rahman (2005) showed that there is no evidence that DSE is weak form efficient by using technical trading rule. Islam and Khaled (2005) analyzed on the predictability of the share price in Dhaka Stock Exchange prior to the boom in 1996 and found evidence in favor of short-term predictability of share prices in the Dhaka stock market prior to the 1996 boom. In order to test whether CAPM is a good indicator of asset pricing in Bangladesh, Rahman et al (2006) considered Fama and French (1992) methodology on five variables (Stock market return, Beta, Book to market value, Market capitalization and Sales) and found that the variables have significant relationship with the stock return.…”
Section: Studies In Dse Marketmentioning
confidence: 99%
“…To contribute to economic development, it has to be ensured that investors get desirable returns from it. In that respect, Dhaka Stock Exchange is not weak-form efficient (Hasan, 2004), but a counter argument is given by Islam and Khaled (2005) who found that it was weak-form efficient after the crash of 1996 due to steps taken by Securities and Exchange Commission.…”
Section: Introductionmentioning
confidence: 99%